Developments in soil classification, land use planning and policy implications : innovative thinking of soil inventory for land Use planning and management of land resources - Taha, Faisal K.; Abdelfattah, Mahmoud A.; Shahid, Shabbir A. (Springer Netherlands, 2013)
This important addition to the technical literature of ecology is a storehouse of information on soil that includes inventories, material on databases, and details of policy developments. Soil may be just brown dirt to most people, but its sustained health is vital to the world's ecosystems, and it is under threat as never before from contamination, degradation and salinization, among other issues. Yet soil is a precious resource: it is the essence of life, the location of innumerable chemical reactions, a filtration and nutritive system for water itself, and a versatile, if vulnerable, growing medium. Care is needed in looking after soil, since it renews itself only slowly. As the world's population continues to expand, maintaining and indeed increasing agricultural productivity is more important than ever, though it is also more difficult than ever in the face of changing weather patterns that in some cases are leading to aridity and desertification. The absence of scientific soil inventories, especially in arid areas, leads to mistaken decisions about soil use that, in the end, reduce a region's capacity to feed its population, or to guarantee a clean water supply. Greater efficiency in soil use is possible when these resources are properly classified using international standards. Focusing on arid regions, this volume details soil classification from many countries. It is only once this information is properly assimilated by policymakers it becomes a foundation for informed decisions in land use planning for rational and sustainable uses.